2005
DOI: 10.1111/j.1365-2672.2005.02749.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-field gel electrophoresis, plasmid profiles and phage types for the human isolates of Salmonella enterica serovar Enteritidis obtained over 13 years in Taiwan

Abstract: Aims: Plasmid profile, phage typing, and pulsed-field gel electrophoresis (PFGE) patterns of 124 Salmonella Enteritidis strains isolated in 1998-2002 in Taiwan were analysed and the results were compared with those of the 63 strains obtained in 1991-1997, so that molecular subtypes and epidemic strains for Salmonella Enteritidis over a 13-year period (1991-2002) could be elucidated. Methods and Results: A total of 124 strains of Salmonella Enteritidis isolated from human in Taiwan between 1998 and 2002 were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 35 publications
4
29
0
7
Order By: Relevance
“…Because SE is one of the most genetically homogenous serotypes of Salmonella (Saeed et al, 2006), methods with high discriminatory power are needed. Traditionally, SE isolates have been characterized by phage typing (PT), a universally applied phenotypic method (De Lappe et al, 2009;Pang et al, 2005). The major advantage of PT is that it is a globally accepted method and specific phage type numbers can be assigned to isolates, which makes comparison between isolates possible on a worldwide scale.…”
mentioning
confidence: 99%
“…Because SE is one of the most genetically homogenous serotypes of Salmonella (Saeed et al, 2006), methods with high discriminatory power are needed. Traditionally, SE isolates have been characterized by phage typing (PT), a universally applied phenotypic method (De Lappe et al, 2009;Pang et al, 2005). The major advantage of PT is that it is a globally accepted method and specific phage type numbers can be assigned to isolates, which makes comparison between isolates possible on a worldwide scale.…”
mentioning
confidence: 99%
“…But, phage typing frequently fails to discriminate between outbreak-related and unrelated isolates [17]. In recent years, many DNA-based genotyping techniques have been utilized to delineate epidemiological relationships between various isolates [23,32]. But, the combination of several methods including phage typing, serotyping, antibiogram and genetic typing may provide a powerful discriminatory tool for the epidemiological analysis of unrelated and related Salmonella strains [14,16].…”
mentioning
confidence: 99%
“…This finding is in agreement with a study reported by Liebana et al (2001) in which the majority of S. enteritidis strains isolated from English poultry farms belonged to a single XbaI-PFGE pattern. Similarly, other workers (Thong et al, 1995;Pang et al, 2005Pang et al, , 2007 have reported that the genome of S. Enteritidis strains isolated from human and animal origins in areas geographically far apart from (Germany, Malaysia, Switzerland, Thailand ) each other were found to be highly similar by PFGE. Unfortunately, we have not included some of the reported strains as control strains in our PFGE to evaluate their genetic relatedness with our strains.…”
Section: Discussionmentioning
confidence: 56%